Clustering Batik SMEs: Open Innovation for Environmental Sustainability - Amelia Kurniawati; Fahmy Habib Hasanudin; Fandi Achmad; Raihan Abdurrahman; Rizki Fajar Ahmad Gurnita (Engineering Proceedings, 2025)
Environmental sustainability is challenging for SMEs, mainly due to SMEs’ limited resources. To achieve environmental sustainability, SMEs must innovate their production process and waste management. SMEs can utilize open innovation to counter their limited resources problem. This study aims to explore the clustering of SMEs based on their environmental sustainability achievement and the utilization of open innovation to achieve it. The data used in this study are from 38 SMEs that produce Batik and are located in Rembang Regency, Indonesia. The clustering process is performed using the K-Means algorithm. The results show that the data are grouped into two clusters. The first cluster, with 26 entities, tends to have higher environmental sustainability achievement and open innovation involvement than the second cluster with 12 entities. Therefore, the second cluster needs more attention from external stakeholders to encourage and support them in achieving environmental sustainability, primarily related to using environmentally friendly materials in production.